Early warning analysis of electricity sales based on multi-factor correlation analysis - Hai CHEN; Yan - yan CUI; li MA; Wei LIU; Jun WANG; Shuai YUAN; Ju Guo; Yi HUANG; Xiao–jing Dong (E3S Web of Conferences, 2018)
Under the background of the slowdown in macroeconomic growth and the gradual liberalization of the power system reforming market, the competition pressure of power grid companies in the electricity sales market has intensified, and the growth of power sales is not optimistic. It is necessary to conduct research and analysis of electricity sales. This paper conducts the analysis with the following steps: first, determines the leading, coincident, lagging economic indicators based on multi-factor correlation analysis, then synthesizes early warning index, forecasts electricity sales, finally, achieves early warning of external risks to improve the company's management quality of the electricity sales.